1995
DOI: 10.1161/01.atv.15.8.1131
|View full text |Cite
|
Sign up to set email alerts
|

Mildly Oxidized LDL Induces Platelet Aggregation Through Activation of Phospholipase A 2

Abstract: Native LDL and LDL oxidized under various conditions were compared in terms of their ability to activate platelets. Native LDL did not induce platelet shape change or aggregation, even at high concentrations (2 mg protein/mL). LDL was mildly oxidized with either CuSO4 (mox-LDL) or 3-(N-morpholino)sydnonimine (SIN-1-LDL). Analysis of mox-LDL and SIN-1-LDL showed a small increase of dienes (E234nm from 0.28 +/- 0.04 to 0.55 +/- 0.09, mean +/- SD) and thiobarbituric acid-reactive substance (from 0 to 10.6 +/- 1.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(107 citation statements)
references
References 57 publications
2
101
0
4
Order By: Relevance
“…In our short-term incubation of fresh aorta rings, we used LDL with a limited amount of lipid hydroperoxides, Յ 30 nmol/mg of cholesterol, a concentration 10 -20 times lower than in copper-oxidized LDL, usually referred to as ox-LDL [32], and in the "minimally oxidized LDL" obtained by storage for 2-4 months [26]. Notably, the level of lipid hydroperoxides in our minimally oxidized LDL is below the detection limit of usual analytical tests, so that unless a chemiluminescence method is used, they would be considered as native "nonoxidized" LDL.…”
Section: Discussionmentioning
confidence: 99%
“…In our short-term incubation of fresh aorta rings, we used LDL with a limited amount of lipid hydroperoxides, Յ 30 nmol/mg of cholesterol, a concentration 10 -20 times lower than in copper-oxidized LDL, usually referred to as ox-LDL [32], and in the "minimally oxidized LDL" obtained by storage for 2-4 months [26]. Notably, the level of lipid hydroperoxides in our minimally oxidized LDL is below the detection limit of usual analytical tests, so that unless a chemiluminescence method is used, they would be considered as native "nonoxidized" LDL.…”
Section: Discussionmentioning
confidence: 99%
“…Even after 30 minutes of LDL-platelet contact, the release of 14 C-serotonin was the same as in LDL-free suspensions (Ͻ5% of maximal). Also, Weidtmann et al 49 reported that native LDL failed to induce dense-granule secretion. However, Kaplan et al 50 reported that ␣-granule secretion precedes dense-granule secretion at low concentrations of thrombin, collagen, and Ca 2ϩ -ionophore, resulting in release of minor amounts of granular fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased production of nitric oxide by HDL inhibits platelet activation and adhesion. Finally, activation of phospholipase A2 by oxidized LDL promotes platelet aggregation and adhesion 30 ; therefore, reversal and/or prevention of LDL oxidation by normal HDL prevents oxidized-LDL-mediated platelet activation 31 (FIG. 2).…”
Section: Biologic Functions Of Normal Hdlmentioning
confidence: 99%